Tracking SDG 7 : The Energy Progress Report 2020 - International Energy Agency; International Renewable Energy Agency; United Nations Statistics Division; World Bank; World Health Organization (World Bank, Washington, DC, 2020)
Tracking SDG7: The Energy Progress Report provides the international community with a global dashboard to register progress on the targets of Sustainable Development Goal 7 (SDG7): ensuring universal energy access, doubling progress on energy efficiency, substantially increasing the share of renewable energy, and enhance international cooperation to facilitate access to clean and renewable energy by 2030. It assesses the progress made by each country on these targets and provides a snapshot of how far we are from achieving SDG7. The report is a joint effort of the International Energy Agency (IEA), the International Renewable Energy Agency (IRENA), United Nations Statistics Division (UNSD), the World Bank, and the World Health Organization (WHO), which the United Nations (UN) has named as global custodian agencies, responsible for collecting and reporting on country-by-country energy indicators for reporting on SDG7. The report updates progress with the latest available data up to 2018 for energy access, and 2017 for clean energy. The 2020 release is the sixth edition of this report, which was formerly known as the Global Tracking Framework (GTF).